Teaching & learning English literature - Chambers, Ellie; Gregory, Marshall W (Teaching & learning the humanities in higher education., 2006)
The book is for beginning and experienced teachers of literature in higher education. The authors present a comprehensive overview of teaching English Literature, from setting teaching goals and syllabus planning through to a range of student assessment strategies and methods of course or teacher evaluation and improvement.